INTEGRATION TECHNOLOGY SYSTEMS VARIOUS PARTIES FOR SUPPLY CHAIN SUPPORT - Shania ArifiannissaAnanda Balqish; HafidhioTianjie Masykur (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Supply Chain Management is the most important component in a company because it greatly determines the level of success of a company in carrying out its business processes. Therefore, every business entity must have in-depth knowledge of supply chain management, so that it can carry out all plans and strategies that are deemed suitable to meet the expected expectations of the business it runs. This case study relates to a paving block manufacturing company where the supply chain management process of this business has 3 entities to carry out its business processes, the three entities including producers as sellers of paving block products, suppliers as suppliers of raw materials needed by producers, and customers as end-users (RP Kampstra, J. Ashayeri, JL Gattorna, 2013). Problem-solving solutions are directed at the use of information technology systems for business processes that are run based on needs and conformity to the problems or constraints faced in carrying out supply chain activities. In carrying out their business activities, the three entities involved in the supply chain that were built still experience various obstacles, so that these constraints have a continuous impact that can cause unexpected losses of course. Constraints between these entities that often occur, such as 1) for the producer: ordering raw materials that takes a long time, which can cause lead time (Bernardo Villarreal and Lucy Salido, 2016); promotion and customer service are still manual, so market coverage is limited; the production of various reports is still traditional, so it is prone to errors; monitoring of material delivery activities is also still constrained because the monitoring process is limited to using the telephone. 2) for suppliers: delivery of raw materials to producers which takes a long time; Promotion and provision of product information have difficulty, due to the absence of special media from suppliers that can make it easier for producers to obtain this information. 3) for the consumer: orders can only be made by visiting the producer directly; monitoring of goods delivery can only be limited to using telephone media; it is difficult to obtain product information and producer company data. In overcoming these problems, it is necessary to use information technology as an integrated system that will integrate the needs of the three entities (T. N. Varma, D. A. Khan, 2014) which in this case is called the electronic supply chain (eSCM).